Computing Potential Evapotranspiration by Different Methods - Umamaheshwara, V; Murty, K P.R.V (Annals of Arid Zone, 2016)
Potential evapotranspiration (PET) values at twenty two stations in semi-arid region of south India were evaluated by using {he three methods (Diffusion. Thornthwaite, Penman). Comparison of monthly and .annual values of PET by the three methods revealed PET values by diffusion method to be .close 10 those by Peanman method.